PENERAPAN TEORI PEMROSESAN INFORMASI UNTUK MENINGKATKAN EFEKTIVITAS PEMBELAJARAN BERBASIS DARING DI SMA NEGERI 1 LAWANG KIDUL - Siska Wulandari; Jossiselfiah; Anna Damayanti; Kasinyo Harto; Irja Putra Pratama (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of digital technology has transformed the learning paradigm from conventional systems to online-based models. The COVID-19 pandemic accelerated this transformation; however, the effectiveness of online learning still faces various challenges, particularly in terms of student engagement, concentration, and information retention. This study aims to analyze the application of Information Processing Theory in online learning at SMA Negeri 1 Lawang Kidul, assess its effectiveness, and identify supporting and inhibiting factors in its implementation. The research employed a descriptive qualitative approach using observation, interviews, and documentation methods involving teachers and eleventh-grade students. The findings indicate that the application of Information Processing Theory through strategies such as material segmentation, the use of interactive multimedia, and the provision of immediate feedback can enhance students’ focus, engagement, and memory retention. Learning outcomes significantly improved from an average score of 74.8 to 88.6 after implementing these strategies. The main supporting factors include teachers’ readiness in digital learning design and technological infrastructure support, while the primary obstacles involve network limitations and variations in students’ digital literacy skills. These findings affirm that online learning design based on cognitive theory can enhance learning effectiveness, as it aligns with the mechanisms of human memory.